PRICES OF INFRASTRUCTURE PROJECTS AND FACTORS OF THEIR DEVELOPMENT IN TODAY’S SURROUNDINGS - N. N. Lavrova (Вестник Российского экономического университета имени Г. В. Плеханова)
Today we face the necessity to raise efficiency of infrastructure building. One way to resolve the problem is to design the theoretical foundation of price-making for infrastructure projects. The article studies price-making of infrastructural projects in construction industry in times of weak economic growth, intensifying sanction pressure, economic and political uncertainty. The research is based on methodology of system approach to information generalization, which is obtained from academic sources, analysis of trends of construction industry development. By reviewing Russian and overseas sources the essence and functions of prices of infrastructure building projects were identified. The algorithm of stage making of these prices was shown. The hierarchical system of the life cycle of price-making for infrastructural projects was built on the basis of the international standard ICMS (The International Construction Measurement Standards). The author studied factors of price-making for infrastructural projects. According to the author, price-making for infrastructural project is stipulated by orientation to implementation of the complex plan of modernization and extension of main infrastructure. Designing the theoretical base could provide an opportunity to integrate the practice of infrastructure project implementation into it. The author givesrecommendations on further researching the prices for infrastructural projects with regard to different scenario ofeconomic conditions.